2019
DOI: 10.1111/dom.13802
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes remission 1 year after an intensive lifestyle intervention: A secondary analysis of a randomized clinical trial

Abstract: Aim To investigate whether an intensive lifestyle intervention induces partial or complete type 2 diabetes (T2D) remission. Materials and methods In a secondary analysis of a randomized, assessor‐blinded, single‐centre trial, people with non‐insulin‐dependent T2D (duration <10 years), were randomly assigned (2:1, stratified by sex, from April 2015 to August 2016) to a lifestyle intervention group (n = 64) or a standard care group (n = 34). The primary outcome was partial or complete T2D remission, defined as n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 27 publications
0
47
0
1
Order By: Relevance
“…Until recently it was not known or accepted that Type 2 diabetes remission was possible at all (12), suggesting that standard dietary management approaches are not effective for achieving this. Although there is now evidence that Type 2 diabetes remission is possible with a number of approaches [including Mediterranean (166) and low fat diets (167)(168)(169)], the evidence is strongest for very low energy diets (129,170) and VLCDs (38,130). The former of these methods, very low energy diets, is different in nature to a VLCD however as it is only a short-term approach; thus a long-term, sustainable dietary approach still needs to be adopted after the weight loss phase to ensure any weight that has been lost is not regained, which would almost inevitably lead to the return of Type 2 diabetes.…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
“…Until recently it was not known or accepted that Type 2 diabetes remission was possible at all (12), suggesting that standard dietary management approaches are not effective for achieving this. Although there is now evidence that Type 2 diabetes remission is possible with a number of approaches [including Mediterranean (166) and low fat diets (167)(168)(169)], the evidence is strongest for very low energy diets (129,170) and VLCDs (38,130). The former of these methods, very low energy diets, is different in nature to a VLCD however as it is only a short-term approach; thus a long-term, sustainable dietary approach still needs to be adopted after the weight loss phase to ensure any weight that has been lost is not regained, which would almost inevitably lead to the return of Type 2 diabetes.…”
Section: Type 2 Diabetes Remissionmentioning
confidence: 99%
“…The U-TURN trial, a 12-month lifestyle intervention including high exercise volume and dietary counselling was successful in reducing glucose-lowering medications in 73.5% of patients in the intervention group [ 14 ]. At one-year follow-up, the study showed that remission was achieved and maintained in a group with short disease history (a small subgroup of 14 patients out of 64) [ 15 ]. In general, few patients sustain lifestyle modifications and a meta-analysis indicates that the positive outcomes achieved decline after a trial ends [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…To avoid relapse of the disease, maintenance of behavioural changes is essential. Adherence to lifestyle interventions is a specific challenge for future programmes, as concluded by a three-year follow-up of the Finnish Diabetes Prevention Study [ 5 ], while the U-TURN trial concluded that “further studies on maintaining a lifestyle change are needed” [ 15 ]. It is clearly difficult to sustain long-term lifestyle changes [ 7 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even though most participants achieved substantial weight loss, remission was achieved by two participants, or 13% of the study population. Higher remission numbers have been reported previously [ 41 , 42 ], although some caution should be taken in directly comparing remission numbers across studies due to differences in the definitions used for T2D remission [ 18 ]. Additionally, our study population is relatively small compared to some landmark trials.…”
Section: Discussionmentioning
confidence: 93%